New approach of a contact detection algorithm based on a Shortest Link method (2022)
Contact detection algorithms based on a Common Plane (CP) are among the most used and investigated, despite not being the most optimal when generating a CP and thus detecting the existence of contact between particles. The generation of the CP is quite expensive in computational terms, for which some algorithms seek to check a possibility of contact between them quickly; and then verify it. For these cases, there are algorithms such as the Shortest Link Method (SLM) that efficiently generate a CP and quickly verify the existence of contact between particles. However, this algorithm has some shortcomings. The main reason for this research is to create a new algorithm based on SLM that can work without its disadvantages.